A Comparative Investigation on the Tribological Performance and Physicochemical Properties of Biolubricants of Various Sources, a Petroleum-Based Lubricant, and Blends of the Petroleum-Based Lubricant and Crambe Oil. Issue 6 (1st November 2020) - Soltani, Mohammad Ebrahim; Shams, Kayghobad; Akbarzadeh, Saleh; Ruggiero, Alessandro
Abstract: The effects of the thermophysical properties of crambe, linseed, and jojoba oils, typical petroleum-based lubricant (PBL), and blends of crambe oil and PBL on their tribological performance were investigated. Biolubricants showed better lubricity (i.e., lower coefficient of friction). At 55 N load, linseed and jojoba oils had the lowest wear and PBL had the highest wear. At 90 and 160 N normal loads crambe and PBL and their blends demonstrated the lowest wear and linseed and jojoba oils presented the highest wear. Crambe oil and PBL lubrication regimes start in a elastohydrodynamic regime at low normal load and transform to a mixed regime at higher normal loads, whereas jojoba oil, linseed oil, and the blend sample of PBL and crambe oil follow a mixed lubrication regime at low normal loads and convert to a boundary lubrication regime as the normal load is increased. Further, results indicated that crambe oil, with the lowest coefficient of friction and wear, high viscosity and viscosity index, and low pour point, has a high potential for partial replacement of PBLs. Graphical abstract in separate file: